ANSYS finite element design of an energy saving magneto-rheological damper with improved dispersion stability - Rashid, Muhammad Mahbubur; Firdaus, Md Meftahul; Hassan, Muhammad Hasibul; Rahman, Mohammed Ataur (Springer, 2015)
The magnetorheological (MR) damper is one of the utmost progressive applications of asemi-active damper. Uninterrupted controllability in both on and off state is an important factor of its plenitude application. Current research is attempting to make the damper more effective and efficient by minimizing the existing limitations such as MR fluid’s sedimentation, power consumption and temperature rising, and design optimization. We have broadly analyzed the optimization of MR dampers design with finite element simulation where various parameters of the MR damper have been considered for more accurate results. A prototype MR fluid has been prepared by coating the carbonyl iron particles with xanthan gum to reduce sedimentation. The SEM and Turbiscan results noticeably verify the improved sedimentation stability. In addition, a power-saving MR damper model has been developed by finite element analysis using ANSYS software. Prolonged operation raises the damper’s body temperature and degrades the performance. However, in this energy-saving MR damper model the temperature is not rising to a higher value compared to the conventional dampers, and consequently promotes damper efficiency.